Integrating AI and ML into Cyber Threat Intelligence for Enhanced Proactive Security Measures - Aniket Deshpande (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Amidst the fast-paced advancements in the digital realm, ensuring cybersecurity has become of utmost importance for enterprises across the globe. Conventional reactive methods for cybersecurity are inadequate in addressing the complex and constantly evolving nature of cyber threats. Consequently, there is an increasing requirement to implement proactive security measures that utilize cutting-edge technologies like Artificial Intelligence (AI) and Machine Learning (ML). Integrating AI and ML techniques to improve the ability to recognize and respond to potential threats in a proactive manner. This paper examines the benefits, difficulties, and future possibilities of incorporating AI and ML into cyber threat intelligence by thoroughly analyzing current literature and case studies. The results of this study indicate that AI and ML-based cyber threat intelligent systems provide substantial benefits in terms of identifying, examining, and addressing threats, eventually enhancing an organization’s cybersecurity position.